1985
DOI: 10.2527/jas1985.604998x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vitamin A and β-Carotene on Reproductive Performance in Gilts

Abstract: The effects of vitamin A and beta-carotene on various reproductive parameters were examined in 108 crossbred gilts. Gilts were fed a diet free of vitamin A and beta-carotene for 5 wk, then assigned to one of eight treatments. Statistical comparisons were performed on three sub-groupings of these treatments as follows: (1) DEFICIENT (received 2,100 IU of vitamin A X head-1 X d-1, (2) FED (received dietary supplementation of 0, 2,100 or 12,300 IU vitamin A and (or) 0, 32.6 or 65.2 mg beta-carotene X head-1 X d-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 0 publications
4
28
0
1
Order By: Relevance
“…Changes in concentrations of plasma vitamin A (retinol, retinyl palmitate) and β-carotene throughout the experimental period are shown in Figure 1. The plasma retinol concentrations were in agreement with the literature values [1,3,27]. Over the whole feeding period there were no differences within or between the differently fed animals concerning retinol.…”
Section: β-Carotene and Vitamin A In Plasmasupporting
confidence: 80%
See 2 more Smart Citations
“…Changes in concentrations of plasma vitamin A (retinol, retinyl palmitate) and β-carotene throughout the experimental period are shown in Figure 1. The plasma retinol concentrations were in agreement with the literature values [1,3,27]. Over the whole feeding period there were no differences within or between the differently fed animals concerning retinol.…”
Section: β-Carotene and Vitamin A In Plasmasupporting
confidence: 80%
“…Reports have been made of 10-fold greater levels in plasma, but they contain no information on the amount of β-carotene in the feed [5]. The same group could not detect any β-carotene in the plasma of gilts fed up to 65.2 mg β-carotene per day [3]. This amount represents approximately one fifth of the amount fed in this study.…”
Section: β-Carotene and Vitamin A In Plasmamentioning
confidence: 76%
See 1 more Smart Citation
“…In addition, OPU performed at 3-or 4-day intervals is a scheme that can be used for up to 4 consecutive months (Petyim et al 2003) and has been shown to yield more oocytes per session and embryos from each oocyte batch collected at 3-day intervals (Merton et al 2003), although we found no significant differences between same intervals (data non shown). Our hypothesis is further supported by the fact that retinoid treatment has been previously shown to increase litter size in the gilt (Brief & Chew 1983, Coffey & Britt 1993 and rabbit (Besenfelder et al 1996), and improve embryonic quality without modifying ovulation rates (Shaw et al 1995) in superovulated cows (Shaw et al 1995) and ewes (Eberhardt et al 1999).…”
Section: Embryos Transferred Pregnancy (%)supporting
confidence: 59%
“…There are beneficial effects of β-carotene of D. salina on reproduction reported of various species. β-carotene administration in mice (Chew and Arche, 1983) and pigs (Brief and Chew, 1985;Kostoglou et al, 2000) increased litter size and decreased embryonic mortality. Haliloglu et al (2002) found a positive correlation between beta-carotene level and corpus luteum weight and function of pregnant cattle.…”
Section: Timing Of First Embryo Cleavage and Embryo Quality And Repromentioning
confidence: 99%